Kualifikasi Tindak Pidana terhadap Penggunaan Identitas Orang Lain dalam Transaksi Paylater oleh Anak di Bawah Umur - Aryn Nabiel Budiono; Dewi Muti’ah; Yusaq Djunarto (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The rapid development of Buy Now Pay Later (PayLater) services has facilitated access to digital financing while simultaneously increasing the misuse of other people's identities by minors to obtain credit facilities. Such conduct raises legal issues regarding the proper criminal qualification, as it involves unauthorized use of personal data, manipulation of electronic information, identity forgery, and fraud. This study aims to analyze the criminal qualification of using another person's identity in PayLater transactions committed by minors under Indonesian criminal law. This research employs a normative legal method using statutory and conceptual approaches. Legal materials were analyzed qualitatively using a prescriptive method. The findings reveal that the unauthorized use of another person's identity in PayLater transactions is more appropriately classified as the criminal offense of fraud because the perpetrator intentionally uses another person's identity from the outset to unlawfully obtain credit facilities through deceitful conduct. Violations of the Personal Data Protection Law, the Electronic Information and Transactions Law, and the provisions on forgery under the Indonesian Criminal Code constitute accompanying offenses that reinforce the legal construction of fraud in PayLater transactions. Therefore, determining the appropriate criminal qualification requires a comprehensive approach that considers the characteristics of digital crime and the interrelationship among relevant legal regulations